Relationship between Environmental Factors and Menarche Of 11-14 Year Old Students in Rasht City - Shiva Salehi; Sedigheh Pakseresht; Seyedeh Noshaz Mirhaghjoo; Ehsan KazemnejadLeili (Guilan University of Medical Sciences, 2016)
Introduction: The process of puberty is one of the most important events of one s life and onset of menstruation (menarche) is one of the important phenomena during the maturation process of females. Undoubtedly, genetics is the main determinant factor in the onset of puberty but several environmental factors contribute to the age of menarche. Objective: The purpose of this study was to investigate the association between age of menarche and environmental factors in of 11-14 year old students in Rasht city. Methods: This is a descriptive-analytic study conducted on 700 female students in elementary and secondary schools in Rasht city. The sampling method was conducted on at two-stage cluster random sampling basis. The data were collected by a researcher-designed questionnaire, a tape measure, and a digital scale. The questionnaire was checked for validity by means of content validity. For data collection, the questionnaires with the letters of consent were given to the students who were entitled to take part in the study. The data were analyzed by descriptive and inferential methods such as t-test, chi-square and Cox regression. Results: Mean and Standard deviation of age at onset of menarche was 12.093±0.051years.In examining environmental factors, the results of t-test indicated a significant difference in using cell phones, computer, frequency of use of cell phones during the week, use of a cell phones daily, time of cell phones use during the day, and daily use of computer, use of computer during the day and type of exercise based on Chi square test (P<0.05). The results from Cox regression demonstrated that menstruation occurs statistically more significantly (P<0.05) in girls using the cell phones during the week (RR= 1.028, 95% CI 1.002-1.055) and the daily use of computers (RR=1.242, 95% CI 0.977-1.578). Both of these factors increased chance of occurrence of menarche. Season was another parameter in the occurrence and frequency of menarche as it was found that in spring, menarche has the highest and in winter it has the lowest frequency. Conclusion: In fact, the indicator of health care planning awareness of the age of menstruation is one of the requirements for good health in puberty and fertility. In addition, it is necessary for the youth to have the basic knowledge on time in such a local context with religious and cultural beliefs. Therefore, the findings of this research project can help the managers and planners to run in-service training classes for the health workers in schools to provide the students with the timely proper information in order to prevent the student s wrong performance resulting from excessive use of cell phones and internet and improper information obtained from their peers and unsuitable sources.